Answer:
-41
Step-by-step explanation:
the problem is basically saying that we need to first substitute 5 in for x in the f(x) function first.
then we need to take that answer that we got and substitute it for x in the g(x) function.
i will do this step by step for you
start with the f(x) function
f(x) = 4x + 3
substitute 5 in for x
f(x) = 4(5) + 3
solve
f(x) = 20 + 3
f(x) = 23
now we use our answer from the f(x) function we just solved, and we put it into the g(x) function.
basically you are going to now substitute 23 for x in the g(x) function.
i will also do this step by step for you.
take the g(x) function
g(x) = -2x + 5
substitute 23 for x
g(x) = -2(23) + 5
solve
g(x) = -46 + 5
g(x) = -41
<u>so now your overall answer is -41.</u>
<u>hope this helped!!!! good luck <3</u>